2009
DOI: 10.1021/bi900187s
|View full text |Cite
|
Sign up to set email alerts
|

Humanin Structural Versatility and Interaction with Model Cerebral Cortex Membranes

Abstract: Humanin (HN) is a recently identified neuroprotective peptide able to inhibit neurotoxicity induced by various insults which can be related to Alzheimer disease (AD) as well as to cell death induced by other stimuli. Previous CD and NMR studies demonstrated that HN adopts an unordered conformation in water, a alpha-helix conformation in 30% TFE, and a beta-sheet structure in PBS. Furthermore, other studies clearly indicated HN as a secreted peptide, able to prevent neuronal cell death caused by amyloid beta (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…The spectrum, i.e., a negative descending signal with decreasing wavelength, is essentially characterized as disordered, consistent with the previous data [24]. It has been observed that as the protein concentration was increased, the temperature was raised, or the ionic strength was increased, the HN tends to aggregate and undergo conformational changes [24,28,32]. Thus, the structure analysis was done primarily at 25 • C with 0.1 mg/ml in 10 mM phosphate, pH 7.0, except otherwise indicated.…”
Section: Structure Comparisonsupporting
confidence: 89%
See 2 more Smart Citations
“…The spectrum, i.e., a negative descending signal with decreasing wavelength, is essentially characterized as disordered, consistent with the previous data [24]. It has been observed that as the protein concentration was increased, the temperature was raised, or the ionic strength was increased, the HN tends to aggregate and undergo conformational changes [24,28,32]. Thus, the structure analysis was done primarily at 25 • C with 0.1 mg/ml in 10 mM phosphate, pH 7.0, except otherwise indicated.…”
Section: Structure Comparisonsupporting
confidence: 89%
“…A similar structure transition was also shown in the presence of model cerebral cortex membranes [32]. These results suggest that such a structure change may be prerequisite for the HN to exert neuroprotective activities.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Substitution of Gly for Ser 14 (S14G-HN; HNG) dramatically increases the neuroprotective effect to the same level as that of [DSer 14 ]HN, whereas substitution of Ala for Cys8 (C8A-HN; HNA) abolishes the effect because the molecule can no longer self-dimerize (Hashimoto et al 2001c;Terashita et al 2003). Recently, several groups elucidated the structural features of HN, HNG, and HNA under various conditions (Arakawa et al 2006;Arisaka et al 2008;Benaki et al 2005Benaki et al , 2006Pistolesi et al 2009). However, the structural characteristics of D-Ser-containing HNs, such as [D-Ser 7 ]HN, ] HN,14 ]HN, have not been defined.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noticed that there is a hydrophobic core region “GFSCLLLLTSEID” within the humanin sequence . Humanin can bind hydrophobic pockets of proteins as an α‐helical monomer . It is speculated that HNG might cross the BBB through transporters or humanin receptors on the surface of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%